Analytical method of forming integrated dynamic models and their software implementation - Sytnyk, O.O. (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2012)
У представленій роботі розглядається інтегральний метод динамічного моделювання об'єктів. Запропонований метод має велике значення і дозволяє розв’язувати широкий клас задач математичного моделювання, які можуть бути описані інтегральними рівняннями. Цей підхід дозволяє використовувати нові чисельні алгоритми для вирішення багатьох традиційних проблем за допомогою комп'ютерного моделювання. Розроблене універсальне програмне забезпечення для розв'язання інтегральних рівнянь в MATLAB. In represented work the integral method of dynamic objects simulation is considered. It is shown, that the offered method has a large generality and allows to decide on wide scientific fields of problems of mathematical simulation, which can be described with the integral equations. It is marked, that the offered approach allows to use new numerical algorithms, the number of traditional problems solving by means of computer aided simulation. The universal software for the solution of integral equations in MATLAB is developed.